LEGALITAS IDENTITAS STATUS HUKUM TRANSGENDER DI INDONESIA - Raihana, Raihana; Bilal, Muhammad (ANDREW Law Center, 2025)
In Indonesia, transgender groups face legal issues in recognizing their identity. This article discusses the legal status of transgender, a study of the legality of identity in relation to norms and human rights. This study uses a descriptive normative research method using secondary data, qualitative analysis of the problem of the legal status of transgender based on human rights, the constitution and related population administration regulations. The results of this study found that the legal status of transgender in Indonesia is still weak because there is no regulation. The absence of the state through affirmative policies and constitutional guarantees so that transgender can live with dignity and equality as citizens. Meanwhile, the legality of transgender identity is an inseparable part of the legal system and protection of human rights in Indonesia. In reality, structural and social discrimination continues to occur, thus hindering the recognition of transgender identity, even though there are legal loopholes.